Hermilio Valdizán and the Faculty of Medicine San Fernando - Mariátegui, Javier (1997)
This note is limited to reviewing the step by Hermilio Valdizán sanmarquinas classrooms and mainly by the Faculty of Medicine of San Fernando. Besides his first performance as a student, then as a teacher, all the important historical work focused on the Faculty of Medicine, the Annals of the Faculty of Medicine, the study of Medicine and Medical in Peru is emphasized. Also, the little discussed facet of Valdizán as Secretary of the Faculty who served as more than an administrative fee. The biography of Huanuco teacher is referring to a specific job (Hermilio Valdizán, Psychiatry Project of Peru Lima, 1981). Exams and their contribution to psychiatry and teaching ("Hermilio Valdizán and Psychiatry Peruvian", Lima, 1980), traditional medicine ("Hermilio Valdizán, comparative psychiatry and folk medicine", Buenos Aires, 1980), to psychiatric care, scientific publicismo at periodismo, relevant to specific topics ("Valdizán and the concept of Peruvians, Lima, 1987), etc., are referred to their original sources, in the sake of brevity.